Case Report: Complete atrioventricular block in an elderly patient with acute pulmonary embolism - Kim, Moojun; Seo, Chang-ok; Kim, Hangyul; Kim, Hye Ree; Kim, Kyehwan; Kang, Min Gyu; Park, Jeong Rang (Frontiers in Cardiovascular Medicine, 2024)
Introduction Multiple abnormal electrocardiographic findings have been documented in patients experiencing acute pulmonary embolism. Although sinus tachycardia is the most commonly encountered rhythmic disturbance, subsequent reports have highlighted other findings. These include right bundle branch block, right axis deviation, nonspecific ST segment/T wave changes, and T wave inversion in the right precordial leads. To date, only a limited number of cases involving a complete atrioventricular block have been reported in acute pulmonary embolism. Case presentation Here, we present the case of a 91-year-old woman with acute pulmonary embolism, whose initial electrocardiogram showed a complete atrioventricular block. She presented with presyncope and an initial blood pressure of 77/63 mmHg. Echocardiography confirmed signs of right ventricular dysfunction. Catheter-directed thrombolysis and a temporary pacemaker insertion were carried out sequentially. The following day, electrocardiography showed sinus rhythm with a left bundle branch block. Discussion The presence of a complete atrioventricular block in patients with acute pulmonary embolism serves as a clinical marker of high-risk status.